2019
DOI: 10.1038/s41372-019-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless closure: a versatile treatment for the diverse presentations of gastroschisis

Abstract: Objective Case series have demonstrated sutureless closures to be safe for the correction of gastroschisis. We hypothesize that sutureless closure is efficacious in patients requiring silo reduction without need for intubation. Study design We conducted a retrospective case control study of infants who underwent gastroschisis repair at our institution (January 2011-August 2018). Patient characteristics and clinical outcomes were compared between sutureless closure and primary fascial repair groups. Results Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…El tiempo de ventilación mecánica en relación con lo descrito en la literatura fue mayor, una limitante fue el uso de sedación y relajación. El cierre sin sutura permite reducir la necesidad de ventilación mecánica 11 . Se reportó una media de 129.89 horas contra 163.2 en los pacientes de Witt 8 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…El tiempo de ventilación mecánica en relación con lo descrito en la literatura fue mayor, una limitante fue el uso de sedación y relajación. El cierre sin sutura permite reducir la necesidad de ventilación mecánica 11 . Se reportó una media de 129.89 horas contra 163.2 en los pacientes de Witt 8 .…”
Section: Resultsunclassified
“…Con el paso del tiempo el manejo quirúrgico de la gastrosquisis ha encontrado nuevas formas de cierre: desde el uso de silo, el cierre bajo anestesia y recientemente el cierre sin sutura 11,12 . La literatura menciona que una de las mejores técnicas es el cierre sin sutura, la cual tiene mejor pronóstico al eliminar el uso de anestesia general y el dar la opción de realizarse en la unidad de cuidados intensivos neonatal y no en quirófano; a diferencia del cierre primario con sutura, el cual, además, tiene mayor riesgo de desarrollar complicaciones como el síndrome compartimental; este tipo de cierre tiene un rango de éxito entre el 50 y el 83% dependiendo el estudio 6 , además de que estéticamente no hay cicatriz ni deformidad de la pared abdominal.…”
Section: Discussionunclassified
“…In agreement with other studies, we found that although patients in the sutureless group underwent repair earlier, the two groups had a similar hospital length of stay and time to initiate and reach the goal of enteral nutrition. [3][4][5][6]8 In addition, growth patterns were similar between these two groups through up to 5 years of age, as were the number of hospitalizations during the first year of life, the use of medications for constipation, reflux, or intestinal dysmotil-ity, development of small bowel obstruction, and gastrostomy tube placement. The only long-term outcome that differed between these two groups was the rate of umbilical or ventral hernia repair, which was 24% in the sutureless .…”
Section: Discussionmentioning
confidence: 99%
“…Sutureless repair of gastroschisis was first described in 2004, in which the gastroschisis defect is covered with the umbilical cord and reinforced with medical dress-ings. 1 Sutureless repair can be performed at the bedside and has since been adopted across multiple centers, [2][3][4] with several studies demonstrating that this method reduces mechanical ventilation and the use of general anesthesia compared to the traditional sutured technique. [4][5][6][7][8] While many infants with gastroschisis are born small for gestational age, studies evaluating long-term outcomes have shown that their growth tends to normalize in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…These bags are transparent and allow inspection of the gut for possible necrosis and perforation. 8,15,23,24 Modifications of staged closure technique: Unfortunately, the preformed silo is expensive and unavailable in low-and middle-income countries (LMICs). However, several improvised silo techniques are currently in use in these countries.…”
Section: Types Of Surgical Procedures In Gastroschisismentioning
confidence: 99%